2000
DOI: 10.1515/bc.2000.039
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of PTHrP and PTH/PTHrP Receptor by Extracellular Ca2+Concentration and Hormones in the Breast Cancer Cell Line 8701-BC

Abstract: It was previously reported that 8701-BC breast tumour cells express the gene for parathyroid hormone-related peptide (PTHrP) and PTH/PTHrP receptor (PTHrP-R) and release immunoreactive PTHrP (iPTHrP) into the extracellular medium. Since the regulation of PTHrP and PTHrP-R by breast cancer cells has been poorly investigated so far, we have chosen the 8701-BC cell line as a model system to investigate whether alterations in the extracellular Ca2+ concentration ([Ca2+]e) and treatment with some well-known differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…[12][13][14][15][16] Potential PTH1R transcripts have been detected in breast tissue and in breast cancer cell lines. [17][18][19] PTH-1-34 and PTHrP-1-34 have shown strong evidence for the existence of two distinct regions in the N-terminal and C-terminal domains, and the interaction between the N-and C-terminal domains of PTH-1-34 and PTHrP-1-34 have been reflected in the very weak binding of PTH-15-34 and PTHrP-1-14. 20,21 There is evidence that the PTHrP N-terminal region can sterically hinder receptor binding if certain side chains are modified.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] Potential PTH1R transcripts have been detected in breast tissue and in breast cancer cell lines. [17][18][19] PTH-1-34 and PTHrP-1-34 have shown strong evidence for the existence of two distinct regions in the N-terminal and C-terminal domains, and the interaction between the N-and C-terminal domains of PTH-1-34 and PTHrP-1-34 have been reflected in the very weak binding of PTH-15-34 and PTHrP-1-14. 20,21 There is evidence that the PTHrP N-terminal region can sterically hinder receptor binding if certain side chains are modified.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer was one of the original tumors from which PTHrP was purified and sequenced [17], and it is now known that it is a key factor controlling bone homing and resorption by metastasizing breast cells [2]. Some of us have reported that PTHrP expression by neoplastic breast cells ''in vitro'' is drastically modulated by modifications of the culture microenvironment [18,19]; in addition, data have been produced demonstrating that different PTHrP domains are also biologically-active on breast tumour cells in culture [20][21][22]. In particular, PTHrP (38-94)-amide, administered at 1 nM concentration was found able to restrain growth and invasion as well as to cause striking toxicity and accelerate death of a panel of breast cancer cell lines, the most responsive being MDA-MB231.…”
Section: Introductionmentioning
confidence: 99%
“…Guise et al [17] have shown that PTHrP is a key factor implicated in both the osteotropism of breast cancer metastases, and in breast cancer-mediated bone resorption. Using ''in vitro'' systems, we have demonstrated that PTHrP expression by breast cancer cells can be drastically modulated by modifications of the ''in vitro'' microenvironment [18,19], and that non-N terminal PTHrP domains may exert an effect on the biological behaviour of diverse tumour cell lines [11,12,20,21]. In particular, the midregion PTHrP domain, i.e.…”
Section: Introductionmentioning
confidence: 99%